Performance differences by gender in English reading test - Danuwijaya, Ari Arifin; Roebianto, Adiyo (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
Test fairness becomes an aspect that needs to be considered when developing a test instrument. It is highly recommended that the instrument should not be biased for the test takers by ensuring that they do not behave differently among male and female test-takers. This study aims to examine the extent to which the items in an English proficiency test function differently across gender. Fifty reading items were examined and analyzed using a statistical method for detecting DIF. The items were individually tested for gender DIF using Rasch model analysis with the analysis tool of ConQuest. The results showed that six items were detected for DIF, three of which were basic comprehension items, and the other three were vocabulary questions. Some possible ways of dealing with DIF items were also discussed.